Management of Principal’s Academic Supervision in Improving Teacher’s Professionalism - Idoet, Suaidah; Ahyani, Nur; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to identify and describe the planning and implementation of school principals’ academic supervision to increase teacher’s professionalism, as well as the identification and description of the school principals’ academic supervision follow-up. This study focuses on school principals’ oversight of academics. A qualitative descriptive method is used in this study. Both primary data and secondary data were used in this study. After conducting research, it was discovered that the school principal’s academic supervision planning had been successful in raising the professionalism of the teachers at SMP Negeri 2 Cengal. This planning included developing the supervision program, communicating the goals of academic supervision to teachers, choosing supervision techniques and approaches, and creating supervision assessment tools.